Divergent g‑C3N4‑catalyzed Reactions of Quinoxalin-2(1H)‑ones with N‑Aryl Glycines under Visible Light: Solvent-Controlled Hydroaminomethylation and Annulation - Si, Ya-Feng; Chen, Xiao-Lan; Fu, Xiao-Yang; Sun, Kai; Song, Xiaojie; Qu, Ling-Bo; Yu, Bing (ACS sustainable chemistry & engineering, 2020)
An effective and simple visible light-induced heterogeneous g-C3N4-catalyzed decarboxylative reaction of quinoxalin-2(1H)-ones with N-aryl glycines was developed. When the reaction was performed in DMSO/H2O and EtOH, the products dihydroquinoxalin-2(1H)-ones and tetrahydroimidazo[1,5-a]quinoxalin-4(5H)-ones were unprecedentedly obtained in good yields, respectively. This solvent-dependent system offers advantages, including simple and easy operation, short reaction time, high chemoselectivity, a recyclable catalyst, metal-/base-/oxidant-free, and mild reaction conditions.